Exercise Training Prevents Dexamethasone-induced Rarefaction - Herrera, Naiara A. [UNESP]; Jesus, Isley [UNESP]; Dionísio, Evandro J. [UNESP]; Dionísio, Thiago J.; Santos, Carlos F. [UNESP]; Amaral, Sandra L. [UNESP] (Wolters Kluwer, 2017)
Dexamethasone (DEX) causes rarefaction. In contrast, training (T) prevents rarefaction and stimulates angiogenesis. This study investigated the mechanisms responsible for the preventive role of T in DEX-induced rarefaction. Rats underwent T or were kept sedentary (8 weeks) and were treated with DEX or saline during the following 14 days. Tibialis anterior muscle was used for measurements of capillary density (CD), capillary-to-fiber ratio (C:F ratio), superoxide dismutase CuZn (SOD-1), superoxide dismutase MnSOD (SOD-2), catalase (CAT) mRNA as well as SOD-1, SOD-2, CAT, vascular endothelial growth factor (VEGF), vascular endothelial growth factor receptor-2 (VEGF-R2), cyclooxygenase-2 (COX-2), Bcell lymphoma 2 (Bcl-2), Bd-2-like protein 4 (Bax), p-Bax, and caspase-3 cleaved protein levels. DEX decreased CD (238.1%), C:F ratio (230.0%), VEGF (219.0%), VEGFR-2 (220.1%), COX-2 (222.8%), Bcl-2 (220.5%), Bcl-2/Bax ratio (213.7%), p-Bax/Bax (220.0%) and increased SOD-2 (+41.6%) and caspase-3 cleaved (+24.1%). Conversely, T prevented reductions in CD (+54.2%), C:F ratio (+32.9%), VEGF (+25.3%), VEGFR-2 (+22.2%), COX-2 (+31.5%), Bcl-2 (+35.5%), Bcl-2/Bax ratio (+19.9%), p-Bax/Bax (+32.1%), and caspase-3 cleaved increase (27.8%). T increased CAT mRNA (+21.5%) in the DEX-treated group. In conclusion, T prevented the DEX-induced rarefaction by increasing antioxidant enzymes resulting in a better balance between apoptotic and antiapoptotic protein levels.
Keywords: angiogenesis; apoptosis; glucocorticoids; physical training; skeletal muscle